Using Rgb Image Processing for Designing an Alginate Edible Film - Osorio-Lira, F; Lopez-Angulo, D; Skurtys-Olivier , F; Enrione, J (2012)
The use of edible films to coat food products is a technique that allows for an extended shelf-life. One of the most widely used polymers is calcium alginate. However, this polymer can modify the original food color and the perception by consumers. The objective was to design an alginate film based principally on color changes using a RGB color model. Edible films were prepared with sodium alginate and glycerol as plasticizer, cross-linking the polymer with calcium. Dry and hydrated states of the edible films were studied. Film thickness was directly proportional to surface concentration and increased with hydration. There is a zone in which the color does not change with alginate surface concentration and another where the color is directly proportional to it. This latter scenario is not a consequence of structural changes or the degree of hydration. Results showed a range where the color was not modified by the alginate concentration; hence, an optimal surface concentration was determined as a design parameter. Edible films made using the optimal surface concentration would not mask microbial contamination and have good physical properties (water vapor transmission and swelling) compared with other surface concentrations. In addition, it was possible to model alginate surface concentration as a function of surface color using mathematical tools (clustering, linear regression, and support vector machine), allowing one to study the optimal use of the edible films. © 2010 Springer Science + Business Media, LLC.